New approaches to human dignity in the context of Qur'ānic anthropology : the quest for humanity - Braun, Rüdiger; Cicek, Hüseyin I. (Cambridge Scholars Publishing, 2017)
In recent years, the challenge of relating one's own theological concept of man and his destiny to secular topics, such as the inviolability of human dignity, has generated a dynamic discourse about how Islamic anthropology can help cultivate and perfect the individual self and social 'humanisation'. This anthology brings together contemporary Muslim and non-Muslim approaches to the secular notion of human dignity with reference to the Islamic tradition in general and the anthropology of the Qur'ān in particular. The collection presents approaches to Islamic theological anthropology, across a range of fields, especially with regard to the narrative of Adam and Iblīs, which occurs in all monotheistic traditions. It focuses on the specific 'grammars'of anthropological narratives at the levels of the canonical text of the Qur'ān itself (Section I) and the interpretations that focus on its performative discourse (Section II). Further to this, the normative implications of the human images that are derived from the canonical text and its interpretations are discussed in Section III. The dynamic interdependencies between the hermeneutics of the Qur'ān, theological anthropology and legal philosophy, particularly in the European context, are a promising field of research that not only allows a deeper insight into the multiperspectivity and indexicality of theological anthropology, but also has the potential to facilitate the long-overdue discursive cooperation and rapprochement between Muslim and non-Muslim scholarship.